Analisis Teologis Konsep Pembenaran Berdasarkan Pengakuan Iman Westminster dan Katekismus Heidelberg [A Theological Analysis of the Concept of Justification Based on the Westminster Confession of Faith and the Heidelberg Catechism] - Fergindo Reza Kaligis; Ridwanta Manogu (Universitas Pelita Harapan, 2020)
Both Westminster Confession of Faith and Heidelberg Catechism discuss the core of Reformed teaching on Justification. The purpose of this paper is to analyze the doctrine of justification on both. As the result, the two documents point out similar essences of justification in Reformed theology. It is the work of Jesus Christ in fullfilling satisfaction to his Father’s justice in the elect behalf. Christ’s righteousness is imputed to the believers and their sin to Christ. Double imputation. Faith taking a role as an instrument for God’s people to be justified, and both documents emphasize that it is also God’s grace. Westminster Confession of Faith and Heidelberg Catechism are aligned in teaching the doctrine of justification.